Investigating the Challenges and Barriers of Home Businesses from the Perspective of Business Experts and Owners (Case study of rural communities of Isfahan province) - ahmad hajarian; ahmad taghdisi; hamid barghi (تحقیقات کاربردی علوم جغرافیایی)
ose of this paper is to investigate the barriers and challenges of home businesses from the perspective of home business experts and owners using the Delphi method and confirmatory factor analysis. The purpose of this study is applied research and descriptive-analytical in nature and has a qualitative approach. The statistical population of the study consists of two groups. The first group included experts from the Bureau of Co-operation, Labor and Social Welfare, and the Bureau of Cultural Heritage, Crafts and Tourism, and the second group consisted of home business owners. The sample size for the first group was 28 people using snowball or chain sampling and the second group is based on the statistics of about 1000 people in rural areas of Isfahan province which was determined 276 people according to Cochran formula. Data were analyzed using SPSS 23 software. Delphi technique was used to identify the existing challenges of Isfahan rural communities home businesses. Results in the qualitative part of the study indicated that the most important challenges facing home businesses are structural and managerial factors, policy making, financial and economic, individual-personality, research and information. In the quantitative section, using confirmatory factor analysis, there are 5 factors, namely: financial and economic factors, managerial and structural factors, weaknesses in comprehensive rules and policy, research and information, and personal and personality factors which are 78/73. Explains the percentage of total variance